Persepsi Petani Terhadap Peranan Penyuluh Pertanian Dalam Pengembangan Kelompok Tani Padi Sawah - Muh. Fitrah Hamzah; Faidah Azuz; Aylee Christine Alamsyah Sheyoputri (PALLANGGA: Journal of Agriculture Science and Research, 2025)
Farmers' perceptions of the role of agricultural extension workers are crucial to the success of rice farming groups. The purpose of this study was to determine farmers' opinions on the role of agricultural extension workers in the development of rice farming groups. To achieve this objective, the study was conducted in Belapunranga Village, Parangloe Subdistrict, Gowa Regency, involving 135 farmers. The research data was collected using the Likert scale technique. Based on the analysis using the Likert scale, it can be concluded that farmers' perceptions of the role of agricultural extension workers in Belapunranga Village are categorized as satisfactory. Farmers are satisfied with the knowledge and guidance provided by agricultural extension workers. Persepsi petani terhadap peranan penyuluh pertanian sangat menentukan keberhasilan pengembangan kelompok tani padi sawah. Tujuan penelitian ini untuk mengetahui pendapat petani terhadap peranan pernyuluh pertanian dalam pengembangan kelompok tani padi sawah. Untuk memenuhi tujuan tersebut, maka penelitian ini dilakukan di Desa Belapunranga, Kecamatan Parangloe, Kabupaten Gowa dengan melibatkan 135 petani. Data penelitian ini menggunakan teknik skala likert. Hasil penelitian ini berdasarkan analisis menggunakan skala likert maka dapat disimpulkan bahwa persepsi petani terhadap peranan penyuluh pertanian di Desa Belapunranga dikategorikan memuaskan. Petani merasa puas dengan layanan pengetahuan dan pendampingan yang ddiberikan oleh penyuluh pertanian.